DEVELOPMENT OF ECONOMIC SECTORS IN REGIONS IN THE CONTEXT OF DIGITAL ECONOMY: THEORY, PRACTICE AND PROSPECTS - Nomazov, Bakhrom Bobomuradovich (THE INNOVATION ECONOMY, 2026)
This article examines the theoretical foundations, current state, and prospects for developing economic sectors in the regions of Uzbekistan in the context of the digital economy. The paper analyzes regional economic development, the impact of digital technologies on industries, and the integration of smart cities, artificial intelligence, Big Data, and IoT into regional economies. Reforms implemented in Uzbekistan, particularly the strategy for developing the digital economy until 2030 and its regional aspects, are reviewed. Research results indicate that digital transformation creates opportunities to increase efficiency across all sectors of regional economies by 25-40%.